A study on depression and/or anxiety among adult type 2 diabetes mellitus patients attending diabetic center, Hospital Universiti Sains Malaysia - Roshana, Mohamed Yasin (2008)
To determine the prevalence of depression and/or anxiety and the factors associated with depression and/or anxiety among patient with Diabetes Mellitus in USM. This is a cross sectional study involving 260 adult Type 2 Diabetes Mellitus patients, attending Diabetic Center, HUSM from November 2007 till March 2008. The patients were interviewed using a set of questionnaires on sociodemographic, family dynamic and medical history. Screening for depression and anxiety was done by using self administered Hospital Anxiety and Depression Score. Those who had score of9 and above for both part are positive for anxiety and depression. They were referred to psychiatrist for further assessment to confirm the diagnosis by means ofDSM-IV criteria. The prevalence of depression was 20.8% and anxiety was I 0.8%. Level of occupation (p<0.05), satisfaction with income (p<O.OS), retired and also working in private sector (p<O.OS), source of income from other family members (p<0.05), has been taken care by their children during an acute illness (p<O.OS), diabetic foot and retinopathy (p<0.05) and compliant to the diabetic follow up (p<0.05) were associated with depression. Factors that associated with anxiety were male (p<0.05), decision making in the family (p<0.05), has been taken care by their children during illness (p<0.05) and presence of diabetic foot (p<0.05).Prevalence of depression among T2DM was similar with most studies but however the prevalence of anxiety was lower in this group of patients. Working in private sector, received source of income from other than family members, taken care by their children during acute illness, presence of diabetic retinopathy and diabetic foot were associated with increased risk for depression among T2DM. Those who received secondary and tertiary level of education, satisfied with their income and retired were associated with reduced risk for depression. Those who had diabetic foot was associated with increased ri sk for anxiety, however male and those who occasionally dominance in making decision in making the decision in the fa mily were associated with reduced risk for anxiety.